BIOCHEMICAL PROFILE OF HYDATID CYST FLUIDS OF ECHINOCOCCUS GRANULOSUS OF SHEEP IN DUHOK AREA: S.M.AL-BAYATI ,O.H.AZIZ ,A.M.ABDULL. A . S.A.ABED - AL-BAYATI, S. M. (The Iraqi Journal of Veterinary Medicine, 2010)
Twenty two ( 11 from lung and 11 from liver of lung-liver cross infection ) hydatid cysts fluid collected from sheep slaughter in Duhok abattoir and there biochemical analysis done for several parameters (total protein , Glucose, Cholesterol , triglyceride, creatinine , Urea , Uric acid , Calcium and Magnesium ions ) by colorimetric assay kits for the first time in this area . The biochemical parameters varies in there measures as for protein increased significantly ( P<0.01) in lung cysts fluid ,while in liver some increased significantly like cholesterol ( P<0.01) ,triglyceride ( P<0.05 ) , creatinine (P<0.01) , calcium (P <0.01) and magnesium ( P<0.05). In compare with previous studies the results reflected some differences for many values ,and also among lungs or livers , which may pointed some strain variability in parasite metabolism, growth rate or even strain variation